Numerical investigation of indirect freeze desalination using an ice maker machine. (15th July 2018) - Jayakody, Harith; Al-Dadah, Raya; Mahmoud, Saad
Highlights: CFD modelling of indirect freeze desalination process for an ice maker machine. Salt separation process was modelled for pure water separation from rejected brine. CFD model validated experimentally using a commercially available ice maker machine. The developed CFD model was used to conduct parametric analysis. 2nd freezing process done to reduce salinity to accepted limits for potable water. Abstract: To overcome the water shortage problem, sea water desalination is a prospective answer in order to cater for the escalating demand for fresh water. Freeze desalination is where the freezing of sea water permits the separation of salts from the water in order to produce potable water. The ice formed is of pure water as the ice crystal lattice prevents the inclusion of any salts. The lower energy usage of freeze desalination in comparison to other desalination processes is the key advantage; as the latent heat of fusion (333.5 kJ/kg) is about 1/7th that of the latent heat of vaporisation (2256.7 kJ/kg). CFD ANSYS fluent software has been used to simulate the freeze desalination process; results were compared with experimental tests showing a maximum deviation of 0.93% for the temperature change during the ice forming process and the percentage errors obtained for the salinities of ice and brine were 15% and 10.5% respectively. From parametric analysis study, results showed that, as the freezing temperature reduces, the volume of the generated ice block increases, where at 225 K freeze temperature, 5 times more ice was produced compared to that at 257.15 K, but with a high salinity level of 3.02%. Results also showed that the lowest average salinity achieved was 0.5% at an ice layer thickness of around 4 mm using a freezing temperature of 245 K. This is higher than the 0.1% salinity level recommended by the World Health Organization (WHO) standards as safe to drink water. Therefore, a second stage freezing process was applied to this 0.5% saline water to produce the required salinity level. Results showed that the achieved average ice salinity in the second stage of freezing process was below 0.05% which is regarded as good quality drinking water; also freezing at 225 K temperature produced the largest pure ice volume. These results highlight the potential of using freeze desalination to produce drinking water.